2020
DOI: 10.1111/jocn.15238
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of patient participation in haemodialysis

Abstract: Aim and objective To explore how working‐age adults experience patient participation in hospital haemodialysis. Background End‐stage kidney disease is a progressive, chronic condition imposing patients with high treatment burdens and low health‐related quality of life. Patients face multiple medical decisions related to living with kidney failure. Given their frequent interaction with health services, patient participation may be of special value. Design Qualitative design with a narrative approach. Methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
(116 reference statements)
0
19
0
Order By: Relevance
“…Living with a long‐term condition, such as ESKD, is often associated with acquiring extensive recognition of the bodily manifestations of the illness 32 . However, patients may find it difficult to share such experiences, 4,33 particularly if they are not requested or considered appropriate, for example a third of the study participants had experienced less conditions than preferred to partake in terms of sharing their symptoms or having explanations to their symptoms (Figure 4). Rather, a mutual sense of trust and engagement is needed to build confidence in discussing such issues 10,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Living with a long‐term condition, such as ESKD, is often associated with acquiring extensive recognition of the bodily manifestations of the illness 32 . However, patients may find it difficult to share such experiences, 4,33 particularly if they are not requested or considered appropriate, for example a third of the study participants had experienced less conditions than preferred to partake in terms of sharing their symptoms or having explanations to their symptoms (Figure 4). Rather, a mutual sense of trust and engagement is needed to build confidence in discussing such issues 10,34 .…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 2 HD-SCALE and per cent difference between scores The healthcare system itself can often be one of the most formidable challenges to patient participation (Andersen-Hollekim et al, 2020;Kammerer et al, 2007). Our study found that overall nurses underestimated the degree to which patients were interested in performing haemodialysis tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This may imply that increased patient involvement can be beneficial even within facility or hospital‐based haemodialysis units. Nevertheless, dialysis units tend to have an atmosphere of dependency and passivity (Andersen‐Hollekim et al, 2020; Fotheringham et al, 2017), which would appear to contribute to the acceptance of non‐participation of patients by both patients and staff (Angel & Frederiksen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, research suggests that clinicians may overestimate the level of distress that will result from the disclosure of bad news to patients, and underestimate the probability that patients may be aware of, or learn the news from other sources. [34][35][36][37] Patients may in fact be more distressed because of the secrecy surrounding the disclosure and/or the manner and timing of eventual revelations.…”
Section: Disclosure Of Information About Potential Treatment and Risk Of Harm To Patients In Resource-constrained Settingsmentioning
confidence: 99%